2005
DOI: 10.2193/0022-541x(2005)069[0582:nsosao]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Nest Survival of Scaup and Other Ducks in the Boreal Forest of Alaska

Abstract: We estimated variation in nest survival of lesser scaup (Aythya affinis), greater scaup (A. marila), and other common duck species at Minto Flats, Alaska, USA, during 1989USA, during -1993USA, during and 2002USA, during -2003. Daily survival probability of scaup nests, as well as nests of all other duck species, varied with year, date, and nest habitat. Daily survival probability was unrelated to nest age and distance from the nest to water. Average, year-specific nest survival of all ducks at Minto Flats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…Some have found that nest survival declines mid-season (Dinsmore et al 2002;Wilson et al 2007), while others have found positive (e.g. Grant et al 2005), negative (Burhans et al 2002;Jehle et al 2004), or no relationship between time and nest survival (Traylor et al 2004;Walker et al 2005). We found that, among ground-nesting shorebirds, nest survival was depressed during the mid-season in 5 of 8 years while it was higher in the remaining 3.…”
Section: Discussionmentioning
confidence: 44%
“…Some have found that nest survival declines mid-season (Dinsmore et al 2002;Wilson et al 2007), while others have found positive (e.g. Grant et al 2005), negative (Burhans et al 2002;Jehle et al 2004), or no relationship between time and nest survival (Traylor et al 2004;Walker et al 2005). We found that, among ground-nesting shorebirds, nest survival was depressed during the mid-season in 5 of 8 years while it was higher in the remaining 3.…”
Section: Discussionmentioning
confidence: 44%
“…To obtain nests for trapping, we visited ponds and lake shore segments throughout the study area (Fig. ) with crews of 2–6 people walking abreast and using willow switches to search floating vegetation along margins and up to 50 m into uplands (Walker et al ). We selected nests for trapping from across the study area, with the only criterion being appropriate stage of incubation ( < 5 days from predicted hatch; determined by candling eggs [Weller ]) to reduce potential for nest abandonment.…”
Section: Methodsmentioning
confidence: 99%
“…The boreal forest is the second most productive breeding area for ducks in North America and may serve as an important refuge for prairie waterfowl in dry years due to the abundance of permanent wetlands (Derksen and Eldridge , Batt et al , Slattery et al ). However, little is known about the nesting ecology of ducks in the boreal forest (Petrula , Walker and Lindberg , Slattery et al ). Variation in nest‐site selection among species is driven by habitat availability, weather and climate patterns, and predation pressure (Batt et al ).…”
mentioning
confidence: 99%